The redemption of Bobby Love : a story of faith, family, and justice - Love, Bobby, 1950-; Love, Cheryl, 1963-; Tharps, Lori L (Mariner Books, an imprint of HarperCollinsPublishers, 2021)
"The inspiring, dramatic, and heartwarming true account of an escaped convict and his wife of thirty-five plus years who never knew his secret, which captured the imaginations of millions on Humans of New York. Bobby and Cheryl Love were living in Brooklyn, happily married for decades, when the FBI and NYPD appeared at their door and demanded to know from Bobby, in front of his shocked wife and children: "What is your name? No, what's your real name?" Bobby's thirty-eight-year secret was out. As a Black child in the Jim Crow South, Bobby found himself in legal trouble before his 14th birthday. Sparked by the desperation he felt in the face of limited options and the pull of the streets, Bobby became a master thief. He soon found himself facing a thirty-year prison sentence. But Bobby was smarter than his jailers. He escaped, fled to New York, changed his name, and started a new life as "Bobby Love." During that time, he worked multiple jobs to support his wife and their growing family, coached Little League, attended church, took his kids to Disneyland, and led an otherwise normal life. Then it all came crashing down. With the drama of a jailbreak story and the incredible tension of a life lived in hiding, The Redemption of Bobby Love is an unbelievable but true account of building a life from scratch, the pain of festering secrets in marriage, and the unbreakable bonds of faith and love that keep a family together. "--